Luis De Valdivia's Ideas and Activity in Defence of the Indigenous Population: a Legal Perspective - Centenera Sánchez-Seco, Fernando (Universidad Hemisferios, 2025)
Luis de Valdivia's ideas and activity in defence of the indigenous population have been studied over the years in fields ranging from history to politics, anthropology, linguistics or ethics. Far fewer scholars have examined them from a legal perspective. This paper takes this latter approach, focusing on the period spanning from the turn of the 17th century until the early 1620s. Specifically, it looks at several manifestations of the Jesuit's legacy in the following areas: the jusnaturalist foundation of the indigenous population's freedom, the correspondence with the positive law that prescribed it, criticism of the regulations establishing slavery, the publication and implementation of the regulations concerning the Defensive War, the denunciation of breaches of those regulations, and the lawmaking process behind various provisions.